Factors Influencing The Intention Decision To Adopt Business Continuity Management Of Public Listed Companies In Malaysia - Lee, Lian Kim (2022)
Business Continuity Management (BCM) is a holistic management practice to face various disasters and safeguard businesses. This study focuses on the perception and organisation structure of non-adopters’ decision to adopt BCM. It is to further understand the factors that hinder the adoption among non-adopters’ in PLC Malaysia. Two sections of Diffusion of Innovation (DoI) theory have been utilised as factors that may influence the decision to adopt BCM. In perceived characteristics of innovation, it found that observability and compatibility have a positive significant effect on the decision to adopt BCM. While relative advantages and complexity does not influence the decision to adopt BCM. The second section measuring the internal organisation structure notices that organisation with centralisation structure will hinder the adoption. Specialisation and interconnectedness in the organisation can foster adoption behaviour among non-adopters. Besides, environmentally sensitive industries are used to moderate the relationship of perceived characteristics of innovation and internal characteristics of organisation structure against the decision to adopt BCM. The environmental sensitive industry is to find any connectivity of companies in high risk and sensitive may have intention to adopt BCM.